Sonidegib in the Treatment of Locally Advanced Basal Cell Carcinoma: A Retrospective Study - Florian Herms; Barouyr Baroudjian; Julie Delyon; Pauline Laly; Pauline Tetu; Celeste Lebbe; Nicole Basset-Seguin (Medical Journals Sweden, 2022)
Sonidegib, a hedgehog pathway inhibitor, is indicated for treatment of locally advanced basal cell carcinoma, based on the results of the BOLT study. However, to date, no real-world study of sonidegib has been reported. An observational, retrospective, single-centre study (PaSoS study) was conducted. The primary objective was to evaluate the efficacy of sonidegib for treatment of locally advanced basal cell carcinoma in a real-world setting. Secondary objectives included modalities of use, tolerability, tumour evolution, and management after discontinuation. A total of 21 patients treated with sonidegib were included from March 2018 to January 2021. The median follow-up was 18.7 months and median exposure 7.0 months. Objective response (OR) rate was 81.0% (n = 17) including 6 (29%) patients with a complete response (CR). Disease control rate was 100%. First tumour response was rapid, with a median time of 2.3 months. Nine (43%) patients underwent surgery after sonidegib discontinuation, and no relapse was observed. All the patients experienced at least 1 adverse event (AE). Muscle spasms were the most frequent AE (n = 14; 67%), followed by dysgeusia (n = 8; 38%) and alopecia (n = 12; 57%). The efficacy and safety profile of sonidegib in this first-to-date real-life trial are consistent with prior results. Overall, real-world evidence corroborated sonidegib efficacy and tolerability as a first-line treatment for locally advanced basal cell carcinoma.